Спеціальні підстави виникнення права державної власності примусового характеру - Кушнерук, Дмитро Володимирович; Kushneruk, Dmytro (ВД "Гельветика", 2019)
Статтю присвячено визначенню нормативних актів, якими регулюються спеціальні підстави виникнення права державної власності примусового характеру, їх аналізу з метою виявлення особливостей окремих видів підстав набуття права державної власності й проблем, що виникають у цій сфері. Проаналізовано окремі види підстав. Виявлено проблеми, що виникають під час проведення реприватизації, реквізиції, конфіскації, ліцитації тощо. Проаналізовано сумісність загальної конфіскації та міжнародних норм щодо захисту права власності, реприватизації й захисту прав приватної власності. Виявлено проблеми в правовому регулюванні реприватизації.

The article is devoted to the definition of legal acts which establish special grounds for the emergence of the state property right of compulsory nature, their analysis in order to identify the features of certain types of grounds for acquiring state ownership and problems that arise in this area. Certain types of grounds for the emergence of the state property are analyzed. The problems that arise during the reprivatization, requisition, confiscation, licitatio, etc. are identified. The specific basis for the state property rights, which is not provided for in the legislation, but must be taken into account, is re-privatization. Since privatization is the basis for the termination of the state property rights, re-privatization is the return to state ownership of property that dropped out of such ownership illegally. Classical re-privatization is a reverse process of privatization, a mechanism for returning property to the state, involves the re-sale of previously privatized property. Sometimes re-privatization is identified with nationalization. However, unlike re-privatization, nationalization is the process of returning of non-state property objects, including previously privatized property, to state ownership for their further use considering the realization of national interests. Another special reason for the emergence of state property rights is the forced sale of property (licitatio). Licitatio refers to the seizure by a creditor of the property of a debtor who has not fulfilled his obligation. In accordance with Art. 10 of the Law of Ukraine “On the Procedure for Repayment of Taxpayers' Obligations to Budgets and State Trust Funds”, the tax authority, in case the taxpayer does not have enough additional sources to repay the amount of tax debt, has the right to sell its other assets. However, the tax authority will not be able to carry out such a sale without a court decision. The compatibility of general confiscation and international standards for the protection of property rights, re-privatization and the protection of private property rights are also investigated in the article. Some problems of legal regulation are identified.
Кушнерук, Д. В. Спеціальні підстави виникнення права державної власності примусового характеру / Д. В. Кушнерук // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. – Одеса : Гельветика, 2019. – Вип. 33. – С. 24-30
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; спеціальні підстави; реприватизація; реквізиція; конфіскація; ліцитація; примусове вилучення майна; право власності; держава; санкція; special grounds; re-privatization; requisition; confiscation; licitatio; compulsory seizure of property; property right; state; sanction